Growth of LaBGeO5 crystal fibers by the micro‐pulling down technique. Issue 1 (19th August 2015) - Assi, F.; Ferriol, M.; Cochez, M.; Aillerie, M.
Abstract : As the direct growth of LBGO fibers from the melt using micro‐pulling down technique was unsuccessful because of its high viscosity, a flux is needed. The study of the LBGO‐LiF phase diagram showed that LiF could be convenient. Several crystal fibers were then grown and characterized by Raman spectroscopy. Addition of B2 O3 to decrease flux evaporation allowed to obtain a white cloudy fiber checked by Raman spectroscopy and SEM. Abstract : The LaBGeO5 compound (LBGO) was prepared by solid state reaction at 1050°C and characterized by XRD and DTA analysis. The direct growth of LBGO fibers from the melt using micro‐pulling down technique was unsuccessful because of its high viscosity. The study of the LBGO‐LiF phase diagram showed that LiF could be considered as a convenient flux to reduce viscosity of the melt during the growth process. Several crystal fibers were then grown and characterized by Raman spectroscopy. To decrease the high volatility of LiF, B2 O3 was added to the melt. A white cloudy fiber was obtained from LiF‐B2 O3 flux and checked by Raman spectroscopy and scanning electron microscopy.